Pengaruh Pemberian Injeksi Intramuskular Sel Punca Mesenkimal Tali Pusat Manusia Terhadap Gambaran Histopatologi Ginjal Pada Tikus Putih (Rattus norvegicus) Galur Sprague dawley yang diinduksi Aspirin - Cahaya Carla Bangsawan; Evi Kurniawaty; Utari Gita Mutiara; Betta Kurniawan (Majority, 2022)
Uncontrolled use of aspirin can cause several complications and various damaged to organs, including kidney injury. Mesenchymal stem cells as an alternative therapy is an important source for repair and regeneration of damaged tissue. The purpose of this study is to determine the effect of intramuscular injection of human umbilical chord on kidney tissue impairment of rats (Rattus norvegicus) with aspirin induction. This study was a laboratory experimental study with a post test only control group design with 27 white rats (Rattus norvegicus) Sprague dawley strain which divided into three groups. The control group (KK) was given regular drink and food, P1 was given 200 mg/kgBW aspirin orally for 14 days, P2 was given 200 mg/kgBW aspirin orally for 14 days and treated with intramuscular injection of 0.75 mL extracted human cord mesenchymal stem cells. Data were observed by Kruskal-Wallis Non-Parametric Test, obtained p=0,001 (p<0,05), then get a meaningful result which means Ho is rejected. The statistical results with Mann-Whitney test obtained are also find significant differences in each groups, but P1 with P2 (p=0,497) has no significant differences.